(untitled) (Jurnal Bahasa, 2001)
This is an introduction to the study of style in the context of the history of the Malay Language. I start with the concept of style. I have to look for a concept which enables me to discuss the problem of style in the context of the study of the history of Malay Language. We are entraped in the many concepts of style: Something statistically dominant and that of deviation. And we also have to pay attention to some particular phenomena. The second part is regarding the data for the study of style. We have to take into account the differences between the "present" and the "old" Malay, and between the Malaysian and the Indonesian Malay. We have to discuss the matter before venturing to a further study. I discuss the matter in the second part of the discussion.